2011
DOI: 10.12973/ejmste/75178
|View full text |Cite
|
Sign up to set email alerts
|

Changing Science Teaching Practice in Early Career Secondary Teaching Graduates

Abstract: Initial teacher education (ITE) is being challenged internationally to prepare teachers with the understandings needed to teach an increasingly diverse student population. Science teachers need to prepare students with both conceptual and procedural understanding. The challenge is to prioritise a balance in ITE courses between theoretical perspectives, curriculum requirements, and pedagogical approaches. This paper presents results of a three-year longitudinal study from pre-service through two years of in-ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A large body of quantitative and observational research grounded in SDT (Ryan and Deci 2017) have demonstrated the importance of students' perception of the teaching style that PE teachers adopt (Ntoumanis and Standage 2009). Most studies have exclusively focused on the 'bright side' of motivational processesthe relations between need-supportive teaching behavior, needs satisfaction, and desired motivational outcomes (Haerens et al 2015;Reeve 2013;Taylor and Ntoumanis 2007;Van den Berghe et al 2013;Van den Berghe et al 2015), whereas more and more studies have started examining the 'dark side'how need thwarting teaching practices, needs frustration, and motivational outcomes are interrelated in various settings, including sport (Bartholomew, Moeed, and Anderson 2010;Stebbings et al 2012), work (Gillet et al 2012), health (Verstuyf et al 2013) and PE contexts (De Meyer et al 2016;Haerens et al 2015).…”
Section: Motivational Outcomes In Physical Educationmentioning
confidence: 99%
“…A large body of quantitative and observational research grounded in SDT (Ryan and Deci 2017) have demonstrated the importance of students' perception of the teaching style that PE teachers adopt (Ntoumanis and Standage 2009). Most studies have exclusively focused on the 'bright side' of motivational processesthe relations between need-supportive teaching behavior, needs satisfaction, and desired motivational outcomes (Haerens et al 2015;Reeve 2013;Taylor and Ntoumanis 2007;Van den Berghe et al 2013;Van den Berghe et al 2015), whereas more and more studies have started examining the 'dark side'how need thwarting teaching practices, needs frustration, and motivational outcomes are interrelated in various settings, including sport (Bartholomew, Moeed, and Anderson 2010;Stebbings et al 2012), work (Gillet et al 2012), health (Verstuyf et al 2013) and PE contexts (De Meyer et al 2016;Haerens et al 2015).…”
Section: Motivational Outcomes In Physical Educationmentioning
confidence: 99%
“…Differences between teachers from different countries are greater than differences between gender or study track. The finding leads to the conclusion, that the most important factor in recognizing the importance of different views on good teaching is rooted in a school culture and values (Opfer & Pedder 2011), culture of the society (Allum et al 2008) and personal belief system (Kagan, 1992;Kreber, 2010) which is changed to more pragmatic and less idealistic approach to teaching during the practice (Bartholomew, Moeed & Anderson, 2011, Bartholomew, Anderson. & Moeed, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This theory refers to a combination of knowledge of content and pedagogy. Moreover, PCK also includes understanding what makes learning specific topics easy or difficult (Bartholomew et al, 2011). Therefore, this study examines science teacher trainees' preparedness to teach content and their proficiency in strategies on how to teach the subject (pedagogy).…”
Section: Resources Needed To Transform Education To Meet 4ir's Needsmentioning
confidence: 99%
“…It is also crucial to recognize that instructing science does not only require knowledge of the content but also an understanding of how to teach the concepts, that is, student teachers need adequate pedagogical content knowledge (PCK) to be effective practitioners and to teach science successfully (Shulman, 1986). PCK development includes learning about approaches for improved classroom practice and instructional strategies from reflective classroom experience (Bartholomew et al, 2011;Blayi et al, 2022;Rahmadi et al, 2020). The infusion of posthuman pedagogy is of importance in finding new teaching and learning pathways (Blaikie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%